2019
DOI: 10.1161/jaha.119.011937
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Trajectories During Young Adulthood and Incident Hypertension: A Longitudinal Cohort in Chinese Population

Abstract: Background This longitudinal study aims to characterize longitudinal body mass index ( BMI ) trajectories during young adulthood (20–40 years) and examine the impact of level‐independent BMI trajectories on hypertension risk. Methods and Results The cohort consisted of 3271 participants (1712 males and 1559 females) who had BMI and blood pressure ( BP ) repeatedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
13
41
0
Order By: Relevance
“…Of the 59 included studies, 19 studies stratified trajectories by sex and 13 studies only included sex‐specific populations (i.e., males only or females only). Two studies 41,66 reported they stratified trajectories by sex, however results were not reported since the results were similar to crude analyses. For most studies, the names and number of trajectories were consistent in both men and women, however visual inspection showed slight differences.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the 59 included studies, 19 studies stratified trajectories by sex and 13 studies only included sex‐specific populations (i.e., males only or females only). Two studies 41,66 reported they stratified trajectories by sex, however results were not reported since the results were similar to crude analyses. For most studies, the names and number of trajectories were consistent in both men and women, however visual inspection showed slight differences.…”
Section: Resultsmentioning
confidence: 96%
“…Of these 22 studies with growth trajectories beginning in childhood, five studies 20,22,38,41,51 had measures until young adulthood (19–23 years old), 12 studies 16,30–32,36,42–50 had measures until midadulthood (38–50 years old), and five studies 5,14,17,18,46 had measures until older adulthood (60–80 years old). The remaining studies ( n = 37) 15,19,21–29,33–35,37,39,40,52–72 did not include any childhood measures, and only included measures >18 years of age. Of these 37 studies that only reported growth measures in adulthood, six studies 26,61–64,70 only included measures during the older adulthood period of life (≥60 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…28 A longitudinal cohort in Chinese population characterized four distinct trajectory groups during adulthood associated with hypertension. 19 To our knowledge, there are no studies that explored the relationship between longitudinal BMI profiles in early to mid-life adulthood and the development of diabetes among Asian population in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple LCGMMs with different trajectory shapes including linear and nonlinear parameters were tested using the strategy we previously described in the online supplementary material. 19 The LCGMM computes estimation of the quadratic curve parameters, including fixed effect parameters (for a group) and random-effect parameters (individual specific). The random effect coefficients represent the difference between the fixed effect parameters and the observed values for each individual.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This method assumes that individual differences in trajectories can be summarized by a finite set of different polynomial functions of time. In the past years, this method has been successfully used to examine the association between BMI trajectories and the risk of hypertension, cancer and all‐cause mortality. However, to date, just a few studies have explored the association between BMI trajectories identified by GBTM and diabetes risk.…”
Section: Introductionmentioning
confidence: 99%